Frenectomy One Hemostat Technique in Patients Using Orthodontic Appliances - Ida Bagus Nyoman Dhedy Widyabawa; Anak Agung Istri Agung Feranasari (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Aberrant frenum in patients with orthodontic appliances installation often causes aesthetic problems and interferes with the movement of teeth during orthodontic activation, especially in cases of midline diastema which often causes relapse of the teeth. Frenectomy one hemostat technique treatment is carried out in this case. Case: A 23-years-old female patient came to the periodontology department of RSGM Saraswati and was referred from the orthodontics department for frenectomy. On examination, it was found that the patient had a high frenum and fibrous tissue in the maxillary anterior midline. Case Management: Asepsis and local anesthesia in the mucobuccal folds of the central and palatal incisors. The fibrous tissue was cut with scissors from the anterior to the palatal midline. Blunt dissection is performed to remove fibrous attachments. The frenum is clamped using the one hemostat technique. Incision of tissue with tissue scissors at the top and bottom of the hemostat. The detached tissue in the form of a triangle is discarded. The edges of the diamond shape wound were sutured with interrupted technique using 4-0 nylon thread. Periodontal dressing placement. Discussion: One week post frenectomy showed the presence of redness and slight oedematus on the mucobuccal fold regio 11 21. At 1 month of follow-up, the healing was found with no tension at the frenum area and fibrous tissue is lost. Conclusion: Frenectomy one hemostat technique can correct a high frenum and can help the success of orthodontic treatment.